The crystal structure of dicarbonyl-(N-nitroso-N-oxido-phenylamine-κ 2 O,O)-rhodium(I), C8H5N2O4Rh - Elmakki Mohammed A.; Gafoor Wesley Abdul; Alexander Orbett T.; Venter Johan A.; Roodt Andreas (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C8H5N2O4Rh, monoclinic, P21/c (no. 14), a = 14.1998(9) Å, b = 3.6516(2) Å, c = 17.7458(11) Å, β = 92.801(2)°, V = 919.06(10) Å3, Z = 4, R gt(F) = 0.0281, wR ref(F 2) = 0.0702, T = 100 K.